2018
DOI: 10.1080/02656736.2018.1526416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative dexmedetomidine on renal function after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: a randomized, placebo-controlled trial

Abstract: Introduction: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) predispose to postoperative renal dysfunction. Dexmedetomidine is an a 2 adrenoreceptor agonist, which has renoprotective effects after cardiac surgery. Objective: To assess the effect of dexmedetomidine on renal function after CRS and HIPEC. Materials: Thirty-eight patients undergoing CRS and HIPEC were randomized to receive dexmedetomidine (dexmedetomidine group, n ¼ 19, loading 1 lg/kg over 20 min followed by inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A total of 19 studies with 3,395 patients were included in the final pooled analyses. [3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23] Of these patients, 1,683 received dexmedetomidine while 1,652 did not. Study review and inclusion is outlined in Figure 1.…”
Section: Manuscript Identification and Characteristicsmentioning
confidence: 99%
“…A total of 19 studies with 3,395 patients were included in the final pooled analyses. [3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23] Of these patients, 1,683 received dexmedetomidine while 1,652 did not. Study review and inclusion is outlined in Figure 1.…”
Section: Manuscript Identification and Characteristicsmentioning
confidence: 99%
“…Intraperitoneal injection of DEX was able to alleviate oxidative stress damage in LPS-induced acute liver injury [14]. Of particular importance is the protective effect of DEX on perioperative AKI revealed in several clinical studies [9,15]. Experimental studies have demonstrated that DEX remarkably attenuates renal oxidative stress and apoptosis in early LPS-induced AKI [16].…”
Section: Introductionmentioning
confidence: 99%
“…In our center, most patients with GI cancer were treated with cisplatin as chemotherapy during HIPEC, including present study, which may be one reason for increased serum Cys-C level. Nevertheless, other factors such as renal hypoperfusion and ischemia caused by intra-abdominal hypertension and heat stress response may play critical roles in the development of AKI [9,20] . We inferred that the elevated serum Cys-C, Cr, BUN and UA may related to HIPECinduced oxidative stress, so the alterations of serum MDA and SOD levels were detected, which are good indicators of the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Dex is a sedative and analgesic drugs widely used in perioperative period, which is a highly selective a2 adrenoreceptor agonist [8] . Previous studies have demonstrated that Dex could protect against tissues injury by preventing oxidative stress [9] . Therefore, we speculated that administration of dexmetomidine during HIPEC may in uence redox state in vivo, and further affect the function of renal and liver as well as patient prognosis.…”
Section: Introductionmentioning
confidence: 99%